Effects of simulated precipitation gradients on nutrient resorption in the desert steppe of northern China - Bai, Liu; Wang, Jing; Wang, Zhongwu; Li, Zhiguo; Ren, Haiyan; Wang, Haiming; Zhang, Guogang; Han, Guodong (Frontiers in Plant Science, 2023)
Background: Changes in rainfall induced by climate change will likely influence the utilization of water resources and affect the nutrient cycle in plants in the water-limited desert steppe. In order to understand the response of nitrogen and phosphorus resorption characteristics of plant leaves to precipitation changes, this study compared the nitrogen (N) resorption efficiency, phosphorus (P) resorption efficiency and influencing factors of plants in a desert steppe through water treatment experiments.Methods: A 4-year field experiment was performed to examine the response and influencing factors of nitrogen (N) and phosphorus resorption efficiency of five dominant plants in Stipa breviflora desert steppe to simulated precipitation change in Inner Mongolia, with four simulated precipitation gradients including reducing water by 50%, natural precipitation, increasing water by 50%, increasing water by 100%.Results: Compared with natural precipitation, increasing water by 100% significantly increased soil moisture, and significantly increased the aboveground biomass of S. breviflora, C. songorica, A. frigida, decreased the N concentrations in green leaves of S. breviflora, Cleistogenes songorica, Artemisia frigida, Kochia prostrata, decreased the N concentrations in senesced leaves of C. songorica, decreased the P concentrations in green leaves of K. prostrata and Convolvulus ammannii, decreased the NRE of S. breviflora. NRE was significantly negatively correlated with N concentration in senesced leaves, and PRE was significantly negatively correlated with P concentration in senesced leaves.Increasing water indirectly reduces NRE by reducing plant leaf green leaves nitrogen concentration, and decreasing water indirectly reduces PRE by reducing soil moisture.